Effects of Microwave Sintering on Properties and Microstructure of Ferromanganese Alloy Powders - Lei Li; Libo Zhang; Linqing Dai; Hongbo Zhu; Guo Chen; Jinhui Peng; Qin Guo (Archives of Metallurgy and Materials, 2018)
Microwave sintering process was employed to agglomerate ferromanganese alloy powders. The effects of sintering temperature, holding time and particle size composition on the properties and microstructure of sintering products were investigated. The results was shown that increasing sintering temperature or holding time appropriately is beneficial to increase the compressive strength and volume density. SEM and EDAX analysis shows that the liquid phase formed below the melting point in the sintering process, which leads to densification. XRD patterns indicate that the main reaction during microwave sintering is the decarbonization and carburization of iron carbide phase. The experiment demonstrate that the optimum microwave sintering process condition is 1150°C, 10 min and 50% content of the powders with the size of –75 μm